Prophylactic proton pump inhibitor use and all-cause mortality in adult sepsis patients: a retrospective analysis based on the MIMIC-IV database - Ma, Chendong; Zhang, Lixin; Wang, Min; Zhang, Feng; Zhang, Lipeng (Frontiers in Pharmacology, 2025)
BackgroundSepsis poses a significant threat to human health, and extensive research has examined the relationship between proton pump inhibitors (PPI) and adverse outcomes in patients with sepsis. However, a consensus on this issue remains elusive. Therefore, this study aims to develop a prognostic model to assess the effectiveness of prophylactic PPI administration in patients with sepsis.MethodsA retrospective cohort study was conducted using the open-access Medical Information Mart for Intensive Care (MIMIC-IV) database. Patients diagnosed with sepsis according to the Sepsis-3.0 criteria were selected for inclusion. The primary outcome of interest was all-cause mortality occurring between 28 and 90 days following prophylactic PPI use. Secondary outcomes included in-hospital and intensive care unit (ICU) mortality, duration of hospital and ICU stays, and the incidence of adverse events. Stepwise Cox proportional hazards regression analysis was performed, and multivariate Cox regression models were developed and evaluated using receiver operating characteristic (ROC) curves. Additionally, Kaplan–Meier curves were utilized to compare patient survival at 28 and 90 days.ResultsThis study included 18,198 sepsis patients. The results demonstrated that prophylactic PPI use was significantly associated with increased 90-day all-cause mortality following ICU admission (P < 0.001). Prediction models incorporating 28-day (training AUC 0.74; 95% CI 0.73–0.75) and 90-day (training AUC 0.73; 95% CI 0.72–0.74) outcomes exhibited superior accuracy compared to conventional CCI and SOFA scores. Notably, prophylactic PPI use reduced ICU stay by approximately 1 day in sepsis patients but did not reduce overall hospitalization. Additionally, PPI administration was linked to adverse events including hypoalbuminemia and opportunistic infections.ConclusionProphylactic PPI use failed to improve 28-day or 90-day survival rates in adult sepsis patients. Although PPI use was associated with reduced ICU length of stay, it did not shorten total hospital stay duration. Additionally, PPI administration was linked to clinically significant adverse reactions.